Prospecção de proteínas bioativas secretadas por fungos filamentosos do gênero Aspergillus - Alves, Thaís Barboni [UNESP] (2017)
Natural products can be produced by organisms from all kingdoms, from prokaryotes to eukaryotes. Among these, filamentous fungi are abundant sources of various metabolites, such as proteins and enzymes, which have been outstanding due to their diverse biological activities, with applications not only in the pharmaceutical and medical areas but also in the materials and food industries and in agriculture. Recently, microbial resistance to available antibiotics and the increasingly of aggressive tumor cell lines, makes urgent the investigation of new bioactive molecules, especially those with low or without toxicity to mammalian cells. Due to the great potential of fungal proteins, as promising molecules with biotechnological applications, the objective of this project was the prospection of bioactive proteins secreted by filamentous fungi of the genus Aspergillus. Among the different species studied, Aspergillus niveus cultured under submerged fermentation (Sbmf), in YPD medium for 120 h, was able to secrete a protein with molecular mass of 19 kDa. The protein was analyzed by mass spectrometry and the peptides identified showed 88 to 100% of identity with other ribotoxins described in the literature, such as α-sarcin, restrictocin and Asp f1. The ribotoxin inhibited, in vitro, the cell proliferation of glioblastoma tumor cell line (up to 32%), melanoma (43%), osteosarcoma (41%) and medulloblastoma (50%) at concentration of 20 μg / mL and incubation for 72 h. The ribotoxin was able to inhibit A. niger growth and did not inhibit the growth of S. aureus, E. coli, T. rubrum and A. fumigatus. The fungus A. niveus was also able to secrete chitinases when cultured under Sbmf in minimal medium containing chitin from crab shells as carbon source. The best period for the enzymatic production was 192 h using minimal medium containing 1% chitin. The enzyme was purified by 80% ammonium sulfate precipitation and molecular exclusion chromatography (Sephadex G-100). The chitinase was purified 1.97-fold with yield of 40%. Showed molecular mass of 44 kDa, optimum temperature and pH of activity at 65 °C and 5.0, respectively, being stable at 60 °C for up to 120 minutes. The values of Km and Vmax were 3.51 mM and 9.68 U/mg of protein, respectively. The enzyme was able to inhibit the A. niger growth, but it was not able to inhibit the A. fumigatus growth. Thus, the fungus A. niveus showed the ability to produce ribotoxins with potential for different biotechnological applications, such as in the construction of immunotoxins, in the production of recombinant allergens, in biological control and in the study of ribosomopathies. Moreover, the filamentous fungus A. niveus was able to secrete a chitinase with potential of application in the treatment of waste of the fishing industry, in the production of chitin derivatives and in the control of fungi and larvae pathogenic of plants.